ANALYSIS OF MUSLIM FRIENDLY TOURISM INDICATORS TOWARD THE NUMBER OF FOREIGN TOURIST VISITATIONS - Agita Arrasy Asthu; Rabiatul Adwiyah (Univeristas Islam Bandung, 2021)
Muslim Friendly Tourism (MFT) ordinarily caters to meet Muslim tourists' needs and lifestyles. Many Muslim-friendly tourist destinations are currently being offered by countries incorporated in the Organization of Islamic Cooperation (OIC). Nonetheless, statistical evidence shows that the number of non-Muslims foreign tourists is far ahead of Muslim travelers. This study aims to analyze the impression of MFT indicators on the number of foreign tourist visits and define specific indicators that have a principal power influencing international visitations to the countries incorporated in the OIC. Panel data regression method with time-series data is processed using Econometric Views (Eviews 9.0) as an analysis tool. The results showed that eight independent variables on the Global Muslim Travel Index (GMTI) collectively affected the dependent variable by 97.49%. The present study found that the family-friendly destination variable has a simultaneous effect of 0.012, yet seven other variables did not significantly influence the number of foreign tourists traveling to countries incorporated in the OIC.